Glacial geomorphology of the central and southern Chilotan Archipelago (42.2°S–43.5°S), northwestern Patagonia - Rodrigo L. Soteres; Esteban A. Sagredo; Patricio I. Moreno; Thomas V. Lowell; Brent V. Alloway (Journal of Maps, 2022)
We present a geomorphic map of the glacial landforms associated with the Golfo Corcovado ice lobe in northwestern Patagonia. Built upon prior studies, our map elaborates on the central and southern sectors of Isla Grande de Chiloé and neighboring islands. Through a combination of remote sensing techniques and exhaustive fieldwork, we identified a suite of ice-marginal, subglacial, and glaciofluvial features created by the Golfo Corcovado ice lobe during four maxima within the last glacial cycle, in none of which the ice-front reached the Pacific coast of Isla Grande de Chiloé. Our mapping builds a foundation and provides insights for future interdisciplinary research on the Late Quaternary sequence of glacial and paleoclimatic events in this key sector of northwestern Patagonia.